Efficacy of dupilumab in prurigo nodularis in elderly patient. Issue 1 (28th December 2019) - Giura, Maria T.; Viola, Riccardo; Fierro, Maria T.; Ribero, Simone; Ortoncelli, Michela
Abstract: Prurigo nodularis (PN) is a chronic disorder, affecting adults, with multiple nodules, typically on the limbs. The treatment is challenging, especially in elderly patients. An 85‐year‐old woman had developed in the last 3 years itch with nodular lesions and erythematous scaly patches and excoriations. The extension of the lesions was evaluated by body surface area (BSA) score and the patient's itch and disease‐related sleep disorders by a Numeric Rating Scale (NRS) from 0 to 10. The Dermatology Life Quality Index (DLQI) and blood chemistry were performed before and during the therapy. At the baseline, the BSA score was 56%. Itch and disease‐related sleep disorders were, respectively, NRS 10 and 5 and DLQI was 9. Total IgE count and lactate dehydrogenase were increased. After starting dupilumab, there was a rapid improvement, especially in pruritus. The patient reported the maximum peak of pruritus every day for 6 months. At this time, the itch almost disappeared and clinically only postinflammatory lesions appreciated, with normalization of the blood tests and without any side effects.